2016
DOI: 10.3892/ol.2016.4918
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recurrence and survival rates in grade 3 endometrioid endometrial carcinoma

Abstract: Abstract. The aim of the present study was to determine risk factors associated with recurrence and survival in patients with grade 3 endometrioid endometrial carcinoma (G3EEC). A retrospective analysis of 117 patients with G3EEC, who were admitted to the Obstetrics and Gynecology Hospital of Fudan University between January 2000 and December 2011, was performed. The χ 2 test or Fisher's exact test were used for the comparison of categorical variables. Kaplan-Meier method was used for estimating recurrence-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
(35 reference statements)
2
10
1
Order By: Relevance
“…There was no difference between age and DFS for 3 years in this study. This is consistent with the previous study which found no significant relationship for the influence of age on the incidence of recurrence in grade 3 endometrial cancer (13). Population of endometrioid type of high risk endometrial cancer with BMI <30 kg/m 2 is in accordance with data from Sanglah General Hospital, Indonesia regarding population from August 2012 to July 2014, which also received distribution of endometrial cancer based on body mass index between 18.5-22.9 kg/m 2 .…”
Section: Discussionsupporting
confidence: 93%
“…There was no difference between age and DFS for 3 years in this study. This is consistent with the previous study which found no significant relationship for the influence of age on the incidence of recurrence in grade 3 endometrial cancer (13). Population of endometrioid type of high risk endometrial cancer with BMI <30 kg/m 2 is in accordance with data from Sanglah General Hospital, Indonesia regarding population from August 2012 to July 2014, which also received distribution of endometrial cancer based on body mass index between 18.5-22.9 kg/m 2 .…”
Section: Discussionsupporting
confidence: 93%
“…With the development of novel anti-cancer therapies, survival of early stage EC has been significantly improved [15]. However, the therapeutic effects of advanced EC remain unsatisfactory owing to the lack of effective anti-cancer therapies [16]. As an alternative approach, accurate prognosis may improve patients' survival by guiding the selection of therapeutic approaches and care programs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that evaluation of MI 1 LNM 5 number of women with lymph node metastasis/total LN 5 number of women who had lymph nodes removed. 2 Ungraded nonendometrioid tumors assigned Grade 3. 3 The effect of being one year older at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastasis (LNM) in endometrial cancer (EC) is a strong prognostic factor for survival. 1,2 However, there is no convincing evidence of the therapeutic benefit of systematic lymphadenectomy (LA) neither in presumed Stage I nor in higher stage disease. 3 Internationally, the use and the extent of LA in EC are debated and the guidelines for recommendations of surgical treatment vary between countries.…”
mentioning
confidence: 99%